Evaluating the Impact of Tax Policy Changes on Economic Growth in South Africa - Mosholi, Keneuwe; Viljoen, Diana; Wyk, Abigail Stiglingh-Van; David, Oladipo Olalekan (International Journal of Economics and Financial Issues, 2025)
This study investigates how tax policy changes affect economic growth in South Africa, focusing on personal income tax (PIT), corporate income tax (CIT), and value-added tax (VAT), alongside the roles of savings and consumption. Using secondary time-series data from 2000 to 2022 and applying a Vector Autoregressive (VAR) model, the study finds that both PIT and CIT negatively influences GDP growth. CIT has the most significant impact—a 1% increase results in a 37.3% drop in GDP—while PIT also contributes to economic decline, though to a lesser extent. In contrast, savings and consumption positively affect growth, with consumption notably boosting GDP. VAT, while included as a key tax, has only a marginal effect on economic performance. The findings suggest that in a developing country like South Africa, the burden and impact of taxation differ from those in more advanced economies. Importantly, the study challenges the common assumption that all forms of taxation support growth equally. It recommends that policymakers consider lowering PIT and CIT to encourage investment and consumption, while also introducing incentives to promote savings. VAT should be regulated to avoid dampening consumer spending. The study concludes by calling for broader research, incorporating other macroeconomic indicators such as employment and investment, to deepen understanding of the full impact of tax policy on economic growth.